2022
DOI: 10.5194/egusphere-2022-637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assimilation of Meteosat Third Generation (MTG) Lightning Imager (LI) observations in AROME-France – Proof of Concept

Abstract: Abstract. This study develops a Lightning Data Assimilation (LDA) scheme for the regional, convection-permitting NWP model AROME-France. The LDA scheme intends to assimilate total lightning, i.e., cloud-to-ground (CG) and inter- and intra-cloud (IC), of the future Meteosat Third Generation (MTG) Lightning Imager (LI). MTG-LI proxy data are created and Flash Extent Density (FED) fields are derived. An FED forward observation operator (FFO) is trained based on modeled, column integrated graupel mass from 24 stor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…(2019) suggest 10-15% higher DE at night than during daytime over the CONUS. (Bateman et al, 2021;Erdmann, 2020) found small differences in GLM day-and nightime DE due to the use of coarse criteria and a limited region, respectively.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…(2019) suggest 10-15% higher DE at night than during daytime over the CONUS. (Bateman et al, 2021;Erdmann, 2020) found small differences in GLM day-and nightime DE due to the use of coarse criteria and a limited region, respectively.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…Different techniques have been used for LDA as follows: (a) The forcing of water vapour and other hydrometeors, with both nudging [22][23][24][25][26][27][28] and 3D-Var [21,29,30], (b) retrieving the convective precipitation and latent heat profile by lightning and adjusting the initial three-dimensional thermo-dynamic field of NWP models [31,32], (c) retrieving the radar reflectivity by lightning and assimilating it in NWP models [33][34][35][36], and (d) forcing convection through the adjustment of thermo-dynamical fields [37]. Attempts to suppress spurious convection through lightning data assimilation have also been reported in the literature [38]. All these studies showed different methods to assimilate lightning in NWP, and most of them improved the forecast of intense and/or abundant rainfall typical of convective and severe weather events.…”
Section: Introductionmentioning
confidence: 99%